Directions For Developing Tour Operator Activities On The Basis Of Modern Economic Mechanisms - Mamadaliev, Ulugbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This study examines the strategic directions for developing tour operator activities on the basis of modern economic mechanisms in the conditions of rapid changes in the global tourism market. The main objective of the study is to analyze the impact of the digital economy, vertical and horizontal integration, and innovative marketing strategies on the efficiency of the tour operator business. The article highlights the role of cost optimization, service diversification, and public-private partnership models in ensuring the economic stability of tour operators. It also provides practical recommendations for the modernization of the tourism industry in the conditions of Uzbekistan.